THOMAS HOBBES VE DEMOKRASİ - Naci İspir (Felsefe Dünyası)
Hobbes is generally regarded as the precursor of modern liberalism because he favours individualism and endorses mental and moral autonomy. Howevers, Hobbes is thought to favour Royalist absolutism and is against democracy. This situation is generally explained in the meaning he seeks in autonomy. Hobbes is against the understanding that autonomy is "self-government". This explanation does not seem to clarify the thought that he is against democracy. This study aims to focus, in detail, on the reasons why Hobbes is against democracy.